Multiple anti-epileptic drug use in children with epilepsy in Mulago hospital, Uganda: a cross sectional study. Issue 1 (December 2016) - Atugonza, Rita; Kakooza-Mwesige, Angelina; Lhatoo, Samden; Kaddumukasa, Mark; Mugenyi, Levicatus; Sajatovic, Martha; Katabira, Elly; Idro, Richard
Abstract Background Seizures in up to one third of children with epilepsy may not be controlled by the first anti-epileptic drug (AED). In this study, we describe multiple AED usage in children attending a referral clinic in Uganda, the factors associated with multiple AED use and seizure control in affected patients. Methods One hundred thirty nine patients attending Mulago hospital paediatric neurology clinic with epilepsy and who had been on AEDs for ≥6 months were consecutively enrolled from July to December 2013 to reach the calculated sample size. With consent, the history and physical examination were repeated and the neurophysiologic and imaging features obtained from records. Venous blood was also drawn to determine AED drug levels. We determined the proportion of children on multiple AEDs and performed regression analyses to determine factors independently associated with multiple AED use. Results Forty five out of 139 (32.4 %) children; 46.7 % female, median age 6 (IQR = 3–9) years were on multiple AEDs. The most common combination was sodium valproate and carbamazepine. We found that 59.7 % of children had sub-therapeutic drug levels including 42.2 % of those on multi-therapy. Sub-optimal seizure control (adjusted odds ratio [ORa ] 3.93, 95 % CI 1.66–9.31, p = 0.002) and presence of focal neurological deficits (ORa 3.86, 95 % CI 1.31–11.48, p = 0.014) were independently associated with multiple AED use but not age of seizure onset, duration of epilepsy symptoms, seizure type or history of status epilepticus. Conclusion One third of children with epilepsy in Mulago receive multiple AEDs. Multiple AED use is most frequent in symptomatic focal epilepsies but doses are frequently sub-optimal. There is urgent need to improve clinical monitoring in our patients.